Lifetime performance of Phule Triveni synthetic cows at an organized farm - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; SINGH, MANVENDRA; SAHOO, S K (The Indian Journal of Animal Sciences, 2017)
The performance records of 509 Phule Triveni cows maintained at RCDP, MPKV, Rahuri (Maharashtra) during 1976 to 2012 were used to estimate heritability and genetic and phenotypic correlation of lifetime performance traits. The mixed model analysis using LSML used for estimation of variance components considering sire as a random effect, season and period of birth and age at first calving groups as fixed effects. Period of birth was significantly influencing almost all the lifetime performance traits, whereas season of birth did not influence any of the trait considered in the study. Age at first calving significantly influenced the LTMY3 and 4, HL and BE. The overall least squares means of 8712±271 kg, 12093±265 kg, 12767±207 kg for LTMY3, LTMY4, ALTMY and 2863±29 days, 1875±28 days and 77.00±0.71% were observed for HL, PL and BE, respectively. Heritability estimates for LTMY3, LTMY4 and ALTMY were medium (0.41±0.26, 0.36±0.32 and 0.15±0.11) for milk yield traits indicating that sire selection on the basis of their progeny performance along with improved management is likely to bring desirable improvement in the herd. Whereas the heritability estimates for HL, PL and BE (0.10±0.12, 0.10±0.12 and 0.01±0.11) were low and had high SE indicating that these traits were influenced by non-genetic causes and can be improved through better management. The genetic and phenotypic correlations of actual lifetime milk yield (ALTMY) with herdlife (HL) and productive life (PL) were very high close to 1 and were comparatively higher than the other lifetime performance traits under study.